2,3,7,8-Tetrachlorodibenzo-p-dioxin enhances CCl(4)-induced hepatotoxicity in an aryl hydrocarbon receptor-dependent manner - Mejia-Garcia, Alejandro (Xenobiotica, 2012)
Cytochrome P4502E1 (CYP2E1) is involved in the biotransformation of several low molecular weight chemicals and plays an important role in the metabolic activation of carcinogens and hepatotoxins such as CCl(4). Induction of CYP2E1 is exerted mainly at posttranscriptional levels through mRNA and protein stabilization, and there is little evidence of xenobiotic induction at the transcriptional level. Previously, we reported microarray analysis data suggesting a decrease in Cyp2e1 gene expression on Ahr-null livers when compared to wild-type mouse livers. The goal of the present study was to determine whether 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD) increased mouse CYP2E1 levels in an AhR-dependent manner and the impact on CCl(4)-induced hepatotoxicity. TCDD treatment induced CYP2E1 mRNA and protein levels in mouse liver, and this effect was aryl hydrocarbon receptor (AhR)-dependent. Moreover, TCDD pre-treatment increased the CCl(4)-induced alanine aminotransferase (ALT) activity, the extent of CCl(4)-induced necrosis, and the number of sinusoidal cells in wild-type animals, while this potentiating effect was not observed in Ahr-null mice. In conclusion, this study revealed that TCDD, probably in an AhR-dependent manner, exacerbated CCl(4)-induced hepatotoxicity through induction of CYP2E1.